Notes on a visit to Yakutskaya ASSR, July 1967 - Armstrong, Terence (Polar Record, 1968)
These notes, which are arranged in no special order, represent some of the facts learnt and impressions received during this visit. I made an earlier visit to the same general area of north-east Siberia in October 1965. The Permafrost Institute [Institut Merzlotovedeniya], Yakutsk The Director, P. I. Mel'nikov, was in Canada for two months on an exchange visit. His Deputies are now F. E. Are, who was here in 1965, and I. I. Tuchkov, a geologist recently transferred from the Yakut Filial to take N. A. Grave's place. These two looked after me in the friendliest and most helpful way.